Immune and haematological parameters of Blackbelly ewes infected with gastrointestinal nematodes - González Garduño, Roberto; López Arellano, María E.; Conde Felipe, Magnolia M.; Mendoza de Gives, Pedro; Aguilar Marcelino, Liliana; Jaso Díaz, Gabriela (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: It is necessary to identify phenotypic traits related to natural resistance against gastrointestinal nematodes (GIN) in order to know the host immunity status in productive ewes. Objetive: To determine haematological and immunological parameters (IgA and IgG) during pregnancy and lactation in Blackbelly ewes naturally infected with GIN. Methods: The number of eggs per gram (EPG), packed cell volume (% PCV), plasmatic protein (PP), and peripheral eosinophils were determined during eight months. In addition, sera and saliva samples were collected to establish IgG and IgA kinetics by indirect enzyme-linked immunosorbent assay (ELISA). Results: The results showed 2,592 ± 2,403 EPG and 22.2 ± 4.0% PCV during lactation and 595 ± 901 EPG and 25.1 ± 2.5% PCV during pregnancy. A higher percentage of Trichostrongylus colubriformis larvae were observed in pregnancy (84 to100%) than in lactation (36 to 44%). The IgA activity in serum samples showed a marked reduction (from 80 to 10%) during lambing for both Haemonchus contortus and T. colubriformis antigens. In saliva samples, IgA activity with regard to the standard decreased from 56% at 60 days to 30% at 45 days before lambing and remained low for 45 days during lactation (23 to 32% activity). The eosinophils numbers were 2.0 x 109 cells L-1 in pregnancy and remained low at 0.7 x 109 cells L-1 in lactation. Conclusion: The studied variables reflect the breakdown of immunity against GIN in Blackbelly ewes before and after lambing.